2020
DOI: 10.3390/cells9040923
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wnt Signaling During In-Vitro Bovine Blastocyst Development and Maturation in Synergism with PPARδ Signaling

Abstract: Wnt/β-catenin signaling plays vital role in the regulation of cellular proliferation, migration, stem cells cell renewal and genetic stability. This pathway is crucial during the early developmental process; however, the distinct role of Wnt/β-catenin signaling during pre-implantation period of bovine embryonic development is obscure. Here, we evaluated the critical role of Wnt/β-catenin pathway in the regulation of bovine blastocyst (BL) development and hatching. 6 bromoindurbin-3'oxime (6-Bio) was used to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 45 publications
(41 reference statements)
0
32
0
2
Order By: Relevance
“…Immature cumulus oocyte complexes (COCs) were retrieved from follicles (2–8 mm diameter) from the ovaries of Korean native Hanwoo cows, obtained from the local slaughterhouse, and placed in physiological saline (0.9% NaCl) at 37.5 °C. The TL-HEPES medium was used for the collection of oocytes, and afterwards submitted to in vitro maturation (IVM) and in vitro fertilization (IVF) as described previously by [ 37 ]. In a brief, the collected oocytes were cultured for 22–24 h in NUNC 4-well plates (Nunc, Roskilde, Denmark) containing IVM medium, composed of tissue culture media-199 (TCM-199) supplemented with 10% (v/v) fetal bovine serum (FBS), 1 µg/mL estradiol-17β, 10 µg/mL follicle-stimulating hormone, 0.6 mM cysteine, and 0.2 mM sodium pyruvate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immature cumulus oocyte complexes (COCs) were retrieved from follicles (2–8 mm diameter) from the ovaries of Korean native Hanwoo cows, obtained from the local slaughterhouse, and placed in physiological saline (0.9% NaCl) at 37.5 °C. The TL-HEPES medium was used for the collection of oocytes, and afterwards submitted to in vitro maturation (IVM) and in vitro fertilization (IVF) as described previously by [ 37 ]. In a brief, the collected oocytes were cultured for 22–24 h in NUNC 4-well plates (Nunc, Roskilde, Denmark) containing IVM medium, composed of tissue culture media-199 (TCM-199) supplemented with 10% (v/v) fetal bovine serum (FBS), 1 µg/mL estradiol-17β, 10 µg/mL follicle-stimulating hormone, 0.6 mM cysteine, and 0.2 mM sodium pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of in vitro culture condition on cellular proliferation and DNA fragmentation was determined with anti-BrdU labelling and terminal deoxynucleotidyl transferase (TdT) 20-deoxyuridine, 50-triphosphate (dUTP) nick-end labeling (TUNEL) assay by using an In Situ Cell Death Detection Kit (Roche Diagnostics Corp., Indianapolis, IN, USA), as explained previously by [ 37 , 38 ]. Briefly, for cell proliferation assay, day-8 BLs were washed and incubated for 6 h with 100 mM BrdU at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vivo and in vitro studies showed that the presence of Oct4 and c-Myc expression is crucial during the preimplantation period of embryonic development, maintenance of cell proliferation, and ICM identity [5,23]. Recently, a study on mouse and bovine embryonic development reported that increased Wnt/β-catenin signaling is also manifested by the up-regulated expression of the PPARδ gene in both the ICM and TE cell population [5,6]. The PPARδ expression maintains the higher cell index ratio by sustaining the proliferative signaling in response to β-catenin/Tcf4 signaling [11].…”
Section: Impact Of Wnt/β-catenin Signaling and Pparδ Activation On Cementioning
confidence: 99%
“…The PPARδ expression maintains the higher cell index ratio by sustaining the proliferative signaling in response to β-catenin/Tcf4 signaling [11]. In vitro studies of mouse and bovine embryos showed that Wnt3 stimulation simultaneously increases the PPARδ and c-Myc expression in ICM and trophoblast stem cells (TSCs) and supports the progressive proliferation event during early development [5,6]. These pieces of evidence highlight the functional importance of PPARδ expression during embryonic development and the maintenance of ESCs' pluripotent state in coordination with the Wnt/β-catenin pathway.…”
Section: Impact Of Wnt/β-catenin Signaling and Pparδ Activation On Cementioning
confidence: 99%
See 1 more Smart Citation